Functional and radiological outcomes of Madelung and Madelung-like deformities corrected with corrective osteotomies of radius with or without ulnar shortening - Dhingra, Parakh; Meena, D. S.; Khurana, Ravi; Samria, Kartik; Vijay, Devanshi (International Journal of Research in Orthopaedics, 2025)
Background: Madelung deformity results from a bony and ligamentous dysplasia at the wrist, leading to palmar displacement of the hand on a shortened, bowed forearm. It is commonly associated with dorsal subluxation and prominence of the ulnar head, which collectively contribute to restricted wrist range of motion. Methods: This study included 15 patients diagnosed with Madelung and Madelung-like deformity, with a mean age of 15 years (range: 10–21 years). All patients underwent clinical and radiographic evaluations. Various surgical techniques were employed, including dorsolateral closed-wedge osteotomy, open-wedge osteotomy, and dome osteotomy. Functional outcomes were assessed using the Modified Mayo wrist score, both pre- and post-operatively. Results: Postoperative analysis revealed statistically significant improvements in wrist range of motion, pain relief, grip strength, radial inclination, and carpal slip. The modified Mayo wrist scores also demonstrated significant postoperative improvement. Conclusions: Our findings suggest that surgical intervention plays a pivotal role in restoring wrist function by enhancing range of motion, increasing grip strength, and alleviating pain, ultimately contributing to improved functional outcomes and patient quality of life.